2016
DOI: 10.1039/c6tb00828c
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence light-up AIE probe for monitoring cellular alkaline phosphatase activity and detecting osteogenic differentiation

Abstract: Alkaline phosphatase (ALP) is an important monophosphate hydrolase during cell mineralization and osteogenic differentiation. Though traditional methods are provided for evaluating the ALP expression in the fixed and lysed cells, at present it is still challenging to monitor the ALP activity in living cells. In this work, three phosphorylated tetraphenylethylene (TPE) probes (TPE-PA, TPE-2PA and TPE-4PA) with different numbers of -PO 3 H 2 groups were synthesized for monitoring the ALP activity. It was found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 37 publications
1
23
0
Order By: Relevance
“…The control monomer P-TPE was also prepared, which is water-soluble but can be aggregated by enzymatic reaction with ALP. 25 Compound 1 was synthesized in 64.0% yield from commercially available benzophenone and 4,4 0dihydroxybenzophenone via an Ti-catalyzed reaction, as described in the literature (Scheme S1 †). 26 A phosphonate ester group was readily incorporated into 1 to produce 2 in 43% yield.…”
Section: Synthesismentioning
confidence: 99%
“…The control monomer P-TPE was also prepared, which is water-soluble but can be aggregated by enzymatic reaction with ALP. 25 Compound 1 was synthesized in 64.0% yield from commercially available benzophenone and 4,4 0dihydroxybenzophenone via an Ti-catalyzed reaction, as described in the literature (Scheme S1 †). 26 A phosphonate ester group was readily incorporated into 1 to produce 2 in 43% yield.…”
Section: Synthesismentioning
confidence: 99%
“…Previouss tudies demonstrated that, severale nzymes such as esterase, pepsin and lysozyme won't affect the enzymatic reactionb etween ALP and the phosphate-containing substrates. [17,31] Hence, in this study,t he selectivity of the probe TPE-CN-pho forA LP detection was tested through incubation of the probe with some common biologically-relevant proteins such as BSA (bovines erum albumin), Trypsin, ChE (cholinesterase), GOx (glucoseo xidase) under the same conditions. As shown in Figure 4b,T PE-CN-pho does not show fluorescence enhancement after incubation with these species.…”
Section: Fluorescence Detection Of Alpmentioning
confidence: 99%
“…[29] As for AIE probes, usuallys ufficientw ater solubility can ensure the probe's good solubility in aqueous solution with almost no emission;w hile upon the probe's reaction with the analyte, the resultant product has low water solubility, thus leadingt oa ggregation with enhanced emission. [19][20][21][22][23][24][25][26][27][28][29] At present,s ome AIE-active probes for ALP detection have been reported; [30][31][32][33][34][35][36][37] for most of these probes, they are based on TPE molecule with relativelyl ow conjugation degree,h ence they usually require short excitation wavelength (e.g. UV light) and exhibit relatively short emission wavelength,w hich could erode the detection accuracy due to autofluorescence of biological samples (which usually involves blue emission).…”
Section: Introductionmentioning
confidence: 99%
“…Most importantly, the detection method does not discern the osteogenic differentiation ability of the cell itself. Given to the high sensitivity and easy operation, fluorescent probes have also been developed for the detection of biomarker, such as MMP13 and ALP, to detect the osteogenic differentiation [ [14] , [15] , [16] ]. Nevertheless, the evaluation of the degree of osteogenic differentiation is not easy to realize based on these strategies.…”
Section: Introductionmentioning
confidence: 99%